Synthesis of a Large‐Sized Mesoporous Phosphosilicate Thin Film through Evaporation‐Induced Polymeric Micelle Assembly. Issue 1 (11th September 2014) - Li, Yunqi; Bastakoti, Bishnu Prasad; Imura, Masataka; Suzuki, Norihiro; Jiang, Xiangfen; Ohki, Shinobu; Deguchi, Kenzo; Suzuki, Madoka; Arai, Satoshi; Yamauchi, Yusuke
Abstract A triblock copolymer, poly(styrene‐b‐2‐vinyl pyridine‐b‐ethylene oxide) (PS‐b‐P2VP‐b‐PEO) was used as a soft template to synthesize large‐sized mesoporous phosphosilicate thin films. The kinetically frozen PS core stabilizes the micelles. The strong interaction of the inorganic precursors with the P2VP shell enables the fabrication of highly robust walls of phosphosilicate and the PEO helps orderly packing of the micelles during solvent evaporation. The molar ratio of phosphoric acid and tetraethyl orthosilicate is crucial to achieve the final mesostructure. The insertion of phosphorus species into the siloxane network is studied by 29Si and 31P MAS NMR spectra. The mesoporous phosphosilicate films exhibit steady cell adhesion properties and show great promise as excellent materials in bone‐growth engineering applications.